2014
DOI: 10.1590/s0080-623420140000300016
|View full text |Cite
|
Sign up to set email alerts
|

The opinion of patients with mental disorder about tobacco and its prohibition in psychiatric hospitalization

Abstract: RESUMENObjetivo: Identificar la opinión de los portadores de trastorno mental sobre el tabaco y su prohibición durante la hospitalización psiquiátrica. Método: Estudio exploratorio con 96 portadores de trastorno mental, tabaquistas, internados en el servicio psiquiátrico de un hospital general. Las entrevistas fueron realizadas individualmente utilizando un instrumento elaborado para este estudio. Se registró el contenido verbalizado en las entrevistas, que fueron transcritos y sometidos al análisis de conteni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Pesquisa brasileira revelou que as pessoas com transtornos mentais veem o uso de tabaco como um suporte para lidar com as dificuldades de convívio com os demais pacientes durante a internação psiquiátrica. 15 Outro indicativo da fragilidade do serviço é que ex-fumantes voltaram a fumar na internação e pacientes que tomaram a decisão de parar de fumar durante sua estadia no hospital não ti-2) A atuação da equipe de enfermagem Embora uma das principais dificuldades que os pacientes psiquiátricos encontravam para descontinuar o uso de tabaco fosse a falta de apoio dos profissionais de saúde, os poucos profissionais que realizavam algum tipo de intervenção eram da equipe de enfermagem.…”
Section: Discussionunclassified
“…Pesquisa brasileira revelou que as pessoas com transtornos mentais veem o uso de tabaco como um suporte para lidar com as dificuldades de convívio com os demais pacientes durante a internação psiquiátrica. 15 Outro indicativo da fragilidade do serviço é que ex-fumantes voltaram a fumar na internação e pacientes que tomaram a decisão de parar de fumar durante sua estadia no hospital não ti-2) A atuação da equipe de enfermagem Embora uma das principais dificuldades que os pacientes psiquiátricos encontravam para descontinuar o uso de tabaco fosse a falta de apoio dos profissionais de saúde, os poucos profissionais que realizavam algum tipo de intervenção eram da equipe de enfermagem.…”
Section: Discussionunclassified
“…Some patients reported that they initiated cigarette smoking following peer pressure from fellow smokers (Ghazaleh et al, 2018). Being in an environment that induced the urge for smoking, witnessing others smoke, and specific social settings were implicated in smoking relapse (Buczkowski et al, 2014;de Oliveira et al, 2014;Ghazaleh et al, 2018).…”
Section: Interpersonal Factorsmentioning
confidence: 99%
“…Despite recognising the hospitalisation period or staying in a smoke-free facility as a good time to reduce or stop smoking, some patients mentioned they would consider quitting after their current admission (de Oliveira et al, 2014;Fallin-Bennett et al, 2018;Ratschen et al, 2010;Wilson et al, 2016). These patients suggested this was due to challenges that discouraged changes in their smoking behaviours, including boredom, lack of activities to indulge in during hospitalisation, stress, unsuitability of the environment to address smoking and a need for a substitution for illicit substances during their treatment.…”
Section: Healthcare Factorsmentioning
confidence: 99%